Q beta replicase template specificity: different templates require different GTP concentrations for initiation. - Blumenthal, T (1980)
Qbeta replicase is notable for its high degree of template specificity. It has been shown to transcribe Qbeta RNA and synthetic polymers containing cytidylate. However, other natural RNAs are not transcribed unless Mn2+ ions are present. The enzyme initiates all RNA synthesis with GTP. In this report it is shown that Qbeta replicase can transcribe heterologous natural RNA species in the absence of Mn2+ if sufficient GTP is present. Each RNA tested requires a different GTP concentration for initiation. These results indicate that the site for the initiating nucleoside triphosphate on Qbeta replicase is strongly influenced by the template. It is proposed that the high degree of template specificity is a consequence of the fact that different templates induce initiation sites with varying affinities for GTP. Two lines of evidence support this idea. First, Mn2+ ions, which reduce template specificity, reduce the concentration of GTP required for initiation. Second, high ionic strength, which decreases transcription of all templates except Qbeta RNA, increases the GTP requirement. The possibility is considered that variable promoter or ribosome binding site strengths could result from a mechanism similar to that proposed here.